ISO 9001: 2000 in brief - Tricker, Ray (Butterworth-Heinemann, 2001)
This "hands on" book provides practical information on how to cost effectively set up an ISO 9001: 2000 compliant Quality Management System. The new ISO 9000:2000 family is an all-encompassing series of standards that lay down requirements for incorporating the management of quality into the design, manufacture and delivery of products, services and software. To achieve its main objectives, ISO 9001:2000 requires the manufacturer, or supplier, to possess a fully auditable Quality Management System consisting of Quality Policies, Quality Processes, Quality Procedures and Work Instructions. It.